HUBUNGAN KEJADIAN STUNTING DENGAN FREKUENSI PENYAKIT ISPA DAN DIARE PADA BALITA USIA 12-48 BULAN DI WILAYAH KERJA PUSKESMAS GILINGAN SURAKARTA - EFENDHI, ARI, Dr.Mutalazimah,SKM.,MKes, Fitriana Mustikaningrum, S.Gz., M.Sc (2015)
Introduction : The prevalency of stunting incident in Indonesia is still high, so does the prevalency of ISPA diseases and diarrhea vincrease. Malnutrition children will easy to suffer ISPA and diarrhea than normal children. And the contrary, the more frequency children got ISPA and diarrhea the worse nutrient status. Objective : The aim of the study was investigate the relationship of stunting incident with ISPA and diarrhea frequency in children age 12-48 months old in public health service Gilingan Surakarta Research Methods : Quantitative research with cross-sectional approach used number of respondent 47 persons that was got by simple random sampling technique. The frequency data of ISPA and diarrhea was gotten by interview, while the high of body was gotten from antropometry measurement. The data analysis used the data figure that person product moment and rank spearman. Results : The incident of ISPA and diarrhea were more often than in stunting children than normal children. Mean while, correlation value of the relationship between stunting incident and ISPA and diarrhea were more than 0,05 The stunting children 85,2% and 14,8% the normal children. The children who have diarrhea incident with often frequency, it occurs to the stunting children 68,7% and 31,3% the normal children. Based on the result above was known that there is not relationship of stunting incident with ISPA to the children, with the correlation value 0,411>α=0,05. There is not relationship of stunting incident with diarrhea frequency to the children, with the correlation value 0,548>α=0,05. Conclusions : To sum up there was no correlation between stunting incident with frequency of ISPA and diarrhea in children with age 12-48 month in Public Health Service Gilingan Surakarta.